Development Instruments Through Confirmatory Factor Analysis (CFA) in Appropriate Intensity Assessment - Saptono, Ari (Dinamika Pendidikan, 2017)
The research aims to develop the valid and reliable measurement instruments of entrepreneurship intention in vocational secondary school students. Multi stage random sampling was used as the technique to determine sample (300 respondents). The research method used research and development with confirmatory factor analysis (CFA). Result of confirmatory factor analysis (CFA) at the second order with robust maximum likelihood method shows that valid and reliable instrument with the acquisition value of loading factor is more than 0.5 (> 0,5) and a significance value of t is more than 1,96 (> 1,96). Reliability test results shows that the value of the combined construct reliability (CR) of 0.97and a variance value extract (VE) to 0.52 is greater than the limit of acceptance CR â‰¥ 0.70 and VE â‰¥ 0.50. The conclusion of the measurement instruments of entrepreneurship intention with three dimensions and 31 items met the standards of validity and reliability in accordance with the instrument development process.